2022
DOI: 10.3390/jrfm15030115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial Innovation and Institutional Quality on Financial Development in Emerging Markets

Abstract: Financial innovation and institutional quality play a key role in financial development. This study investigates the impact of financial innovation and institutional quality on financial development in an emerging markets setting. We used the sample of 17 emerging markets based on the availability of data from the period 1990–2020. Data were extracted from the World Development Indicator database. In this study, panel unit root, fully modified ordinary least squares and Pedroni Integration tests were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…Recently, with the advent of technologies and the inclusion of scientific knowledge in banking, the financial industry underwent a transformation phase and entered into a new era of development. With this innovative emergence of digital and wireless technologies, the banking industry has transformed from the traditional style of banking, where the customer's physical appearance was a must for the banking transaction, to an innovative banking style where financial technology and innovation give birth to branchless banking [5]. An individual can either walk into a bank for his banking transactions or go online and do the same with convenience in terms of time and costs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the advent of technologies and the inclusion of scientific knowledge in banking, the financial industry underwent a transformation phase and entered into a new era of development. With this innovative emergence of digital and wireless technologies, the banking industry has transformed from the traditional style of banking, where the customer's physical appearance was a must for the banking transaction, to an innovative banking style where financial technology and innovation give birth to branchless banking [5]. An individual can either walk into a bank for his banking transactions or go online and do the same with convenience in terms of time and costs.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the financial sector has a significant impact on the economic growth of the nation through the mobilization of accumulated capital into productive sectors Paun et al, 2019;Puatwoe & Piabuo, 2017). Economists have generally reached a consensus on the significant role of financial institutions in economic development (Alawi et al, 2022;Chinoda & Kapingura, 2023;Ustarz & Fanta, 2021). Schumpeter (1934) concluded that the financial sector is an engine of economic growth by funding productive investment.…”
Section: Intelligence Journal Of Multidisciplinary Researchmentioning
confidence: 99%
“…Аналіз останніх досліджень і публікацій з питань розвитку та впровадження фінансових інновацій на рин ку фінансових послуг фізичним особам, домогосподар ствам, а також суб'єктам господарювання свідчить, що під дослідження підпадають доволі різні аспекти діяль ності фінансового ринку та фінансових інновацій та тех нологій. Вітчизняні та закордонні автори приділяють увагу як дослідженню загальних тенденцій на фінансо вому ринку щодо фінансових інновацій [5,6], так і пи танням фінансової інклюзії [7], впливу фінансових інно вацій та інституційної якості на фінансовий розвиток в умовах ринків, що розвиваються [8]. Окремі аспекти реалізації та впровадження фінансових інновацій також досліджуються під час вивчення питань реалізації спе ціалізованих соціальних, екологічних, просторових та інших проєктів, які залучають також активність членів територіальних громад, приватних підприємців, тощо.…”
Section: аналіз останніх досліджень і публікаційunclassified